Tanggung Jawab Perusahaan dalam Memberdayakan Masyarakat Desa Melalui Program CSR di Indonesia - Henni Adlini Hasibuan (Yayasan Literasi Sains Indonesia, 2023)
Corporate Social Responsibility (CSR) is a strategy and phenomenon in which companies accommodate the needs and interests of their stakeholders. Since the era when awareness of long-term corporate sustainability, CSR has played an important role rather than just company profitability. The existence of a form of corporate social responsibility or known as corporate social responsibility (CSR) which can be realized in the form of any program or service activity, is needed to improve good reciprocal relations between companies and the community, especially the people affected by the establishment of the company. The purpose of this research is to find out how the CSR program is a corporate responsibility in empowering village communities. The approach used in this study is a literature review approach, by utilizing literature in the form of journals, books and articles that are relevant to the theme and title of the research. According to the findings of this study, community empowerment is the best strategy for implementing CSR initiatives. Companies that work with rural communities to empower them use human and natural resources to develop new resources to improve social, economic and environmental well-being in the area.